Pengelolaan Kelas Dalam Mengoptimalkan Kemampuan Belajar Siswa Kelas 4 B Sd Muhammadiyah Alam Surya Mentari Tahun Pelajaran 2015/2016 Pengelolaan Kelas Dalam Mengoptimalkan Kemampuan Belajar Siswa Kelas 4 B Sd Muhammadiyah Alam Surya Mentari Tahun Pelajaran 2015/2016 - PRANOTO, ANGGUN (2016)
This study aims to determine (1) Describe managing the class 4 B SD Muhammadiyah Alam Surya Mentari. (2) Describe optimize the learning ability of students grade 4 and SD Muhammadiyah Alam Surya Mentari. Methods of data collection in this study was obtained by in-depth interviews, observation, and documentation. This study was a qualitative research deskkriptif analyze a phenomenon in a situation in a manner which conclude the analysis results. The results of this research show that, (1) Implementation of classroom management consists of three activities: planning teachers prepare lesson plan created along with instructional media for guidance when the learning process in the classroom, managing the class consists of two activities, namely, activities rearranging the furniture and environmental facilities learning so that it can support the learning process, activities management behavior provides students with a learning environment that is conducive to learning varied interspersed intermezo and prevent and overcome any interference in the process of learning in students who do not discipline or problems individual ability of students, evaluation was carried out to measure the extent to which the level of students' ability to learn as well as the material of the improvements students and teachers. (2) Optimizing the ability to learn by designing a character takes into account the diversity of learning needs to children's learning abilities. In implementation to provide optimal learning for student teachers to create a conducive learning atmosphere with resolve and prevent any disturbance and the use of methods and learning strategies were mixed. Learning groups are based on study skills so that students with one another can help each other. regulation seating is arranged according to the needs of students who need guidance.